Travel motivations of sport tourists visiting Sabah, Malaysia - Dolinting, Erica E. (2014)
The knowledge on sport tourist behaviours is essential as it can be used as a basis for market segmentation, product positioning, destination development and marketing strategies in tourism. While there is no doubt that Malaysia has a huge potential for the world’s tourism especially in sport tourism. The arrivals of sport tourists to Sabah showed positive growth in spite of the research of sport tourism in Malaysia still at low. The knowledge on the sport tourism in Sabah is still at scarce making it difficult to implement right marketing strategy without the availability of latest sport tourism data. Therefore, it is of extreme importance the information on the sport tourists to be discovered. So, the purpose of this study was to gain knowledge on the sport tourist behaviour based on their desire and needs for travelling and factors that attracted them to visit Sabah. The demographic profiles and travel characteristics were also used for segmenting sport tourism market. The push and pull theory was adopted as research framework. The Leisure Motivation Scale and 23-semantic differential scale instrument were utilized to measure the push motives and pull factors. Analyses of data include descriptive statistics, t-test and logistic regression. A total sample of 301 active sport tourists was drawn from two sport tourism destinations of different districts in Sabah (Sipadan Island and Mount Kinabalu).It was found out that, in both locations, majority of the respondents were international active sport tourists. Comparison between domestic and international active sport tourists were carried out as it would provide a better picture on how much sport tourism market affected the economy of Sabah. Statistically, at Sipadan Island,domestic active sport tourists were significantly more motivated by four push motives than international sport tourists. The four push motives include competencemastery,intellectual, stimulus avoidance and social factors. The main push factor behind active sport tourists visiting Sipadan Island was intellectual motive or the associated feeling of satisfying curiosity, learning new things and expand knowledge as well as learning about self. At Mount Kinabalu, domestic active sport tourists were significantly more motivated by the competence mastery and social motives compare to international active sport tourists. With respect to the pull factors,analysis of result from the logistic regression shows there was no significant difference in perceptions of Sipadan Island between the domestic and international active sport tourists. However, there were few attributes which has been identified to possess impacts at Mount Kinabalu which include busy, crowded, inland, individualistic, adult oriented, inexpensive, safe, far away and international for the international active sport tourists. The domestic active sport tourists on the other hand, perceived Mount Kinabalu as quiet, coastal, deserted, group and family oriented, expensive, risky, close to home and domestic. The findings of this study not only provides theoretical implications but as well implied some practical implications such as (1) certain push motives should be emphasized and then effectively promoted to fulfil the various needs of active sport tourists visiting Sabah at different destinations; (2) market segmentation for sport tourism in Sabah may also be made based on age group and travel characteristics which include type, size and length of vacation and (3) the identification of different perceptions of Mount Kinabalu by domestic and international active sport tourists can be used as a tool for product positioning by tourism marketer.